2018
DOI: 10.1002/mus.26380
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Electrodiagnostic Features Of Nontraumatic Sciatic Neuropathy

Abstract: Introduction: In this study we sought to characterize etiologies and features of sciatic neuropathy unrelated to penetrating nerve trauma. Methods: This investigation was a retrospective review of 109 patients with electrodiagnostically confirmed sciatic neuropathies. Results: Hip replacement surgery represented the most common (34.9%) etiology, whereas inflammatory sciatic neuropathy was seen in 7.3%. Electrodiagnostic testing revealed an axonal neuropathy in 95.4% and a demyelinating neuropathy in 4.6%. Pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
3
15
0
3
Order By: Relevance
“…This group of patients with sciatic neuropathy was mostly young, and had a higher female to male ratio when compared to previous studies. 2,4 Yuen et al 2 previously reported that most of their patients with intact SNAPs revealed mild axonal loss changes with normal or near normal CMAP amplitudes. In our study, a reduction of CMAP amplitude was observed in 10 patients, and sensory sparing were seen in patients with both mild (e.g., patient 5) and severe (e.g.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This group of patients with sciatic neuropathy was mostly young, and had a higher female to male ratio when compared to previous studies. 2,4 Yuen et al 2 previously reported that most of their patients with intact SNAPs revealed mild axonal loss changes with normal or near normal CMAP amplitudes. In our study, a reduction of CMAP amplitude was observed in 10 patients, and sensory sparing were seen in patients with both mild (e.g., patient 5) and severe (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Limited data on 4 patients were included in one prior publication. 4 Sensory complaints of paresthesia, numbness and pain were present in all patients. On exam, reduction of pinprick and/or touch sensation was documented in 10 patients, reduction of vibration sensation in 2, and normal sensory exam in 1.…”
Section: Clinical Informationmentioning
confidence: 87%
See 1 more Smart Citation
“…Perioperative sciatic nerve lesions usually result in weakness of the dorsiflexor muscles of the foot. Other muscles supplied by the sciatic nerve, especially the knee flexor muscles, are often only affected at a subclinical level [42]. This also applies to sensory deficits; hypesthesia of the lateral aspect of the calf and across the entire foot with the exception of the medial aspect only occurs in the context of severe injury.…”
Section: Sciatic Nerve Neuropathymentioning
confidence: 99%
“…1 Drop-foot may be associated with many clinical syndromes, so electrophysiological examinations and imaging studies, as well as clinical and neurological examination findings, are essential in the differential diagnosis. 1,2 Trauma, surgery, injections, infections, inflammation, vascular events, or tumors can cause sciatic neuropathy and up to 16% of cases, it can be idiopathic. 1,3 If any, treatment of the underlying cause, immunosuppressive and supportive treatments, and physical therapy applications can be beneficial.…”
mentioning
confidence: 99%